Assessing quality of health care in the context of patient satisfaction from patients’ perspective among a physical therapy and rehabilitation unit - Turkan Akin (BMC Health Services Research)
Abstract Health service policies are evolving into qualified health care providing best possible outcomes as well as focused on patient satisfaction. Hence the qualification valued health care includes patient satisfaction measurements, it is suggested to get feedbacks during the assessment of outcomes from the patient’s perspective. Aging of the world population accelerates demand on rehabilitation medicine which means recovering impairments so is directly related with quality of life. This study measures the patient satisfaction among 286 patients referring to outpatient clinics and receiving therapy within Physical Medicine and Rehabilitation Unit of City Hospital in Balikesir, Turkey. Results showed 63.4 ± 2.6 years mean of age and female majority (63.6%). Region of therapy included 9.8% for total body, plegic syndromes, 19.6% for neck, 25.2% for shoulder, 21.6% for knee and 23.8% for lumbar regions. Patients are grouped in two according to ‘yes’ or ‘no’ answer of the question ‘Do you agree with you have benefit from applied treatment, does the treatment met your expectations?’. 274 patients (95.8%) were agree with therapy met their expectations. Article discusses one of the valid patient satisfaction questionnaire as evidence based outcome measures. In divisions the means of query scores were 3.9 for technical quality, 4.2 for communication with therapist, 3.6 for physical comfort, 3.9 for communication with secretary, 4.1 for communication with doctor, 3.5 for accessibility and 3.5 for cleanliness. Comparison of means among groups did not seem statistically significant as result of Mann–Whitney U test, p > 0.05. In conclusion in the context of qualified health service providing, it is essential to get feedback from health care receivers to measure satisfaction and this needs improvement of generally valid questionnairres. Improved communication and greater provider sensitivity towards patients can enhance patient satisfaction resulting as meeting the expectation.